(untitled) (Bangladesh Journal of Child Health, 2014)
Xeroderma pigmentosum is an autosomal recessive, rare pigmentary atrophic disease of childhood that progresses to early development of senile changes in sun-exposed skin. Xeroderma pigmentosum (XP) was first described in 1874 by Hebra and Kaposi. In 1882, Kaposi coined the term xeroderma pigmentosum for the condition, referring to its characteristic dry, pigmented skin. Xeroderma pigmentosum is also known as DeSanctis- Cacchione syndrome. DOI: http://dx.doi.org/10.3329/bjch.v38i1.20026 Bangladesh J Child Health 2014; VOL 38 (1) : 40-43